2014
DOI: 10.1098/rspb.2014.1421
|View full text |Cite
|
Sign up to set email alerts
|

Preference for outbred host plants and positive effects of inbreeding on egg survival in a specialist herbivore

Abstract: Inbreeding can profoundly affect the interactions of plants with herbivores as well as with the natural enemies of the herbivores. We studied how plant inbreeding affects herbivore oviposition preference, and whether inbreeding of both plants and herbivores alters the probability of predation or parasitism of herbivore eggs. In a laboratory preference test with the specialist herbivore moth Abrostola asclepiadis and inbred and outbred Vincetoxicum hirundinaria plants, we discovered that herbivores preferred to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 44 publications
1
2
0
Order By: Relevance
“…These results agree with previous findings that host genotypic diversity at the patch or population level increases arthropod abundance (Crutsinger et al 2006, Johnson et al 2006, and that the heterozygosity and genotype of individual hosts may affect herbivore abundance to significant degrees (Evans et al 2012, Kalske et al 2014. Effects of heterozygosity have previously been reported e.g., by Tovar-Sánchez et al (2013), who found total arthropod biomass to decrease with increasing heterozygosity of the host and interpreted this as a potential sign of weaker defense in more homozygous hosts.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…These results agree with previous findings that host genotypic diversity at the patch or population level increases arthropod abundance (Crutsinger et al 2006, Johnson et al 2006, and that the heterozygosity and genotype of individual hosts may affect herbivore abundance to significant degrees (Evans et al 2012, Kalske et al 2014. Effects of heterozygosity have previously been reported e.g., by Tovar-Sánchez et al (2013), who found total arthropod biomass to decrease with increasing heterozygosity of the host and interpreted this as a potential sign of weaker defense in more homozygous hosts.…”
Section: Discussionsupporting
confidence: 82%
“…For example, host genetic diversity may increase the abundance of associated arthropods at the level of individual plants e.g., by herbivore preference (cf. Gripenberg et al 2010, Kalske et al 2014, or at the level of plant populations e.g., by increased resource availability (Crutsinger et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…; this study). Climatic variation, predation, and parasitism of eggs and larvae are likely to be the main contributors to variation in herbivore population size (Förare and Solbreck 1997;Kalske et al 2014a; this study). In a previous study, V. hirundinaria plants from two of four populations were locally adapted to sympatric herbivores (A. asclepiadis) in terms of resistance (Kalske et al 2012) and herbivores from two populations were locally adapted to their host plant (Kalske et al 2012;Laukkanen et al 2012).…”
Section: Study Speciesmentioning
confidence: 80%